Evaluasi Program Kajian Kutub At-Turats Mahasantri Ma’had Al-Jami’ah IAIN Kendari dengan Model CIPP - Anugrah, Rahmat; Nurlathifah Thulfitrah B (Jurnal Budi Pekerti Agama Islam, 2026)
This study aims to evaluate the implementation of the At-Turats Book Study Program using the Context, Input, Process, and Product (CIPP) evaluation model to provide an overview of the program’s relevance, resource readiness, implementation, and outcomes. The research method used is descriptive qualitative, with data collection techniques through observation and interviews. The results show that in terms of context, the study of classical texts meets the needs of the santri and aligns with the vision of Ma’had Al-Jami’ah, which aims to deepen religious and cultural understanding. In terms of input, the program is supported by qualified instructors and representative classical reference books, although there are still limitations in the number of teachers, the varying abilities of the santri, and supporting facilities. Regarding the process, the study is carried out using the halaqah method with a bandongan approach, which is relatively consistent, although the participation and interaction of the santri are limited. Some santri are still hesitant to engage actively in discussions, which can reduce the effectiveness of learning. In terms of product, the program has a positive impact, including an improvement in religious understanding, the development of more moderate and tolerant religious attitudes, and enhanced ability to comprehend classical texts among some of the santri. Overall, the program has achieved its main objectives but still requires improvement in terms of facilities and interaction during the learning process.